Learning about climate change the Pacific way a guide for Pacific teachers - Fiji - Le Bars, Jipé; Sabass, Hanna; Young, Carol (Secretariat of the Pacific Community, 2013)
The guide that go with the visual guide is published in both English and French. Each picture is described and suggestions are made on how to use it. Background information and hands-on teaching activities are provided. The guides include links to the school curricula of Fiji, Kiribati, Samoa, Tonga, Vanuatu and Tuvalu.